1982
DOI: 10.1159/000131791
|View full text |Cite
|
Sign up to set email alerts
|

Cytotaxonomy of the Ciconiiformes (Aves), with karyotypes of eight species new to cytology

Abstract: Somatic karyotypes of 13 species of ciconiiform birds, Phoenicopterus ruber chilensis, Phoeniconaias minor, Cochlearius cochlearius, Geronticus eremita, Threskiornis molucca, T. spinicollis, Balaeniceps rex, Ciconia ciconia, C. nigra, Euxenura maguari, Xenorhynchus asiaticus, Ephippiorhynchus senegalensis, and Leptoptilos crumeniferus are presented. The chromosomes of eight of these species are described in detail for the first time. Of special interest are a case of structural heterozygosity in a male B. rex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
0

Year Published

1984
1984
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 7 publications
8
16
0
Order By: Relevance
“…The morphology of the macrochromosomes observed in M. americana was also similar to that of other Ciconiidae, such as Ciconia ciconia, C. boyciana, Ephipiorhynchus senegalensis (Takagi and Sasaki, 1974), C. maguari (De Boer and Van Brink, 1982), Leptotilos javanicus (Belterman and De Boer, 1984) and Jabiru mycteria (Belterman and De Boer, 1990), although there is a tendency for a reduction in the number of microchromosomes among these species, with E. senegalensis, C. boyciana and C. ciconia having 2n = 68, C. stormi and C. episcopus 2n = 60, J. mycteria 2n = 56 and C. nigra 2n = 52. According to Belterman and De Boer (1990), the chromosome complement of M. cinerea may represent the ancestral karyotype of Ciconiids.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The morphology of the macrochromosomes observed in M. americana was also similar to that of other Ciconiidae, such as Ciconia ciconia, C. boyciana, Ephipiorhynchus senegalensis (Takagi and Sasaki, 1974), C. maguari (De Boer and Van Brink, 1982), Leptotilos javanicus (Belterman and De Boer, 1984) and Jabiru mycteria (Belterman and De Boer, 1990), although there is a tendency for a reduction in the number of microchromosomes among these species, with E. senegalensis, C. boyciana and C. ciconia having 2n = 68, C. stormi and C. episcopus 2n = 60, J. mycteria 2n = 56 and C. nigra 2n = 52. According to Belterman and De Boer (1990), the chromosome complement of M. cinerea may represent the ancestral karyotype of Ciconiids.…”
Section: Discussionsupporting
confidence: 73%
“…Until now no information on the chromosomes of these two species is available, although wide karyotypic diversity has been already reported for other Ciconiiformes, including different species of the Threskiornithidae and the Ciconiidae (Takagi and Sasaki, 1974;De Boer and Van Brink, 1982;De Boer, 1984, 1990;De Boer, 1984;Mohanty and Bhunya, 1990). It has been suggested that the karyotype pattern of Threskiornithids is derived from that of Ciconiids (Takagi and Sasaki, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…identical to those of Ciconia ciconia, C. maguari, Ephippiorhynchus asiaticus and E. senegalensis (De Boer & Van Brink, 1982). It shares the morphology of pairs 1 to 3 with all hitherto studied Ciconiidae and 7 additional pairs of individually recognizable autosome pairs (pairs 4 and 5 subtelocentrics, pair 6 submetacentrics, pairs 7-9 metacentrics of medium to small size, pair l0 acrocentries twice the size of the next smaller pair of autosomes).…”
Section: Ciconi$ormesmentioning
confidence: 66%
“…The first three pairs of large macrochromosomes are of a characteristic morphology that is found in many species of various other orders (e.g. Ciconiidae, Balaenicipitidae and Phoenicopteridae of the Ciconiiformes, Cathartidae of the Falconiformes, Gruidae of the Gruiformes, most Anseriformes, and some species ofColumbiformes; Takagi& Sasaki, 1974;De Boer, 1976;De Boer & Belterman, 1980b;De Boer & Van Brink, 1982). There are two pairs of submetacentric medium-sized macrochromosomes (pairs 4 and 5), while a third pair of similar size (no.…”
Section: Pelecaniformesmentioning
confidence: 99%
See 1 more Smart Citation